REPRESENTASI FATHERLESS DAN DAMPAKNYA TERHADAP PERKEMBANGAN ANAK DALAM FILM "AYAH, INI ARAHNYA KE MANA, YA?" - Alberti Marito Br Sianturi; Raykel Surmana Tarigan; Martha Sitopu; Isma Indriyani; Ita Khairani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the representation of fatherless conditions and their impact on child development as depicted in the Indonesian film "Ayah, Ini Arahnya ke Mana, Ya?" The research employs a qualitative descriptive approach with a semiotic analysis method based on Roland Barthes's theory of signification. The data sources consist of selected scenes, character dialogues, and visual codes in the film that reflect the absence of a father figure. The results reveal that the film constructs three layers of meaning related to the fatherless condition, namely the denotative level showing physical absence, the connotative level depicting emotional dysfunction, and the mythological level reinforcing patriarchal social narratives. In terms of child development impacts, the film represents emotional instability, declining academic motivation, identity-seeking behavior, and disruption of social attachment in child characters. This study also identifies how the language used by characters functions as a medium for expressing and negotiating grief due to paternal loss. The findings contribute to the discourse of Indonesian language and literature education, particularly in the analysis of film narratives as a means of understanding social phenomena that influence children's language and psychological development.